2022
DOI: 10.1002/jmv.28395
|View full text |Cite
|
Sign up to set email alerts
|

Wide mismatches in the sequences of primers and probes for monkeypox virus diagnostic assays

Abstract: Rapid and accurate diagnosis of infections is fundamental to containment of disease. Several monkeypox virus (MPV) real‐time diagnostic assays have been recommended by the CDC; however, the specificity of the primers and probes in these assays for the ongoing MPV outbreak has not been investigated. We analyzed the primer and probe sequences present in the CDC recommended MPV generic real‐time PCR assay by aligning those sequences against 1730 MPV complete genomes reported in 2022 worldwide. Sequence mismatches… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Notably, MPXV isolates of the current outbreak exhibit mismatches in the primer binding sites of both the forward and reverse primer 14 . A recent report indicates a fourfold increase of the LoD of the PCR described by Li et al 10 on the current MPXV subvariants 15 . Since other mutations in the MPXV genome might further increase the LoD of this PCR, we recommend following current guidelines of local health authorities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Notably, MPXV isolates of the current outbreak exhibit mismatches in the primer binding sites of both the forward and reverse primer 14 . A recent report indicates a fourfold increase of the LoD of the PCR described by Li et al 10 on the current MPXV subvariants 15 . Since other mutations in the MPXV genome might further increase the LoD of this PCR, we recommend following current guidelines of local health authorities.…”
Section: Discussionmentioning
confidence: 92%
“…14 A recent report indicates a fourfold increase of the LoD of the PCR described by Li et al 10 on the current MPXV subvariants. 15 we recommend following current guidelines of local health authorities.…”
Section: Clinical Performancementioning
confidence: 99%
“…In order to perform a robust and informative assay, we combined the general (GE) and WA clade-specific (WA) reactions described by Li et al (2010) ( 7 ) with an internal control reaction and demonstrated that the 2 MPXV reactions are sensitive and have very similar kinetics. A recent publication ( 15 ) suggested that changes in primers sequences developed by Li et al ( 7 ) should be made, to render them more suitable to detect the currently circulating MPXV clade. In our reaction design, we addressed this by altering the sequence of the MPXV general (GE) reaction forward primer, already in May 2022, based on genomic analysis of currently circulating MPXV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Wu et al. found variations in the target regions of the monkeypox virus detection primers published by the CDC ( Wu F. et al., 2023 ). These newly emerging variations could lead to an underestimation of the viral load in samples and even result in misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%